(untitled) (Journal of Economic Additions, 2025)
This article aims to identify how to build an artificial intelligence investment strategy for listed startups, based on the experience of the Jahez startup listed on the Saudi Stock Exchange. By using descriptive and analytical approaches, the study concluded that investing in AI requires setting and achieving strategic goals. These goals include making data available at the startup level, training employees to understand, analyze, and use data; leveraging AI analytics to guide and improve strategic decisions; mitigating AI risks and allocating investments to research and development; and enhancing AI collaboration. Keywords: Investment; Strategy; Artificial Intelligence; Startups; Jahez. Jel Classification Codes: L26, O32, M15